The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.3141/1869-05
|View full text |Cite
|
Sign up to set email alerts
|

Field Performance Evaluation of Class C Fly Ash in Full-Depth Reclamation: Case History Study

Abstract: Class C fly ash is a coal combustion product from lignite or subbituminous coal obtained as a result of the power generation process. In recent years, efforts were taken to incorporate self-cementing fly ash into fulldepth reclaimed (FDR) material to improve the structural capacity of asphalt pavement base layers. In this study, existing asphalt pavement in County Trunk Highway (CTH) "JK" in Waukesha County, Wisconsin, was pulverized in place and mixed with fly ash and water to function as a base course. To ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The UCS requirement for a subbase layer (>1700 kPa) was met for all but one mixture of RSG and fly ash, and for only one mixture prepared with RPM (15% fly ash and 28 day cure). Even though the UCS criteria are not satisfied for most cases of RPM, field experience (Hatipoglu et al, 2008;Li et al, 2007;Wen et al, 2004) has shown that RPM and RSG blended with 10-15% fly ash have Downloaded by [Northeastern University] at 23:10 04 January 2015 Table 2. SRM and power model fitting parameters k 1 and k 2 (Eq.…”
Section: Unconfined Compressive Strengthmentioning
confidence: 98%
See 1 more Smart Citation
“…The UCS requirement for a subbase layer (>1700 kPa) was met for all but one mixture of RSG and fly ash, and for only one mixture prepared with RPM (15% fly ash and 28 day cure). Even though the UCS criteria are not satisfied for most cases of RPM, field experience (Hatipoglu et al, 2008;Li et al, 2007;Wen et al, 2004) has shown that RPM and RSG blended with 10-15% fly ash have Downloaded by [Northeastern University] at 23:10 04 January 2015 Table 2. SRM and power model fitting parameters k 1 and k 2 (Eq.…”
Section: Unconfined Compressive Strengthmentioning
confidence: 98%
“…For example, road surface gravel (RSG) from a gravel road undergoing rehabilitation may be reused as the base layer for newly paved roads (Hatipoglu, Edil, & Benson, 2008). Alternatively, recycled pavement material (RPM) (a mixture of pulverised asphalt, base, and possibly subgrade from the existing road) may be used as base course for a new pavement (Wen, Tharaniyil, Ramme, & Krebs, 2004). In some cases, the strength and stiffness of these recycled materials are enhanced by blending them with a cementitious material (Dutta, 2008), such as fly ash from coal-fired electric power plants (Hatipoglu et al, 2008;Li, Benson, Edil, & Hatipoglu, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although application of polymer modifiers is a very effective method to reduce the fatigue cracking, considerable reduction of rut depths and thermal cracking, this solution brings an extra cost in the overall design. In the relevant literature, it was reported that application of fly ash improves the mechanical properties of dense bituminous mixtures [7][8][9][10][11][12][13][14][15][16][17][18] . Therefore using this waste material in order to improve the mechanical properties of the bituminous mixture provides real economy when compared with polymer modifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Current sustainable pavement rehabilitation methods allow for the use of recycled materials instead of virgin materials. Several cases have demonstrated successful use of on-site pavement recycling rehabilitation techniques by transportation agencies (Bemanian, Polish, & Maurer, 2006;Diefenderfer, Apeagyei, Gallo, Dougald, & Weaver, 2012;Lewis, Jared, Torres, & Mathews, 2006;Mallick et al, 2002;Maurer, Bemanian, & Polish, 2007;Miller et al, 2011;Romanoschi, Hossain, Gisi, & Heitzman, 2004;Wen, Tharaniyil, Ramme, & Krebs, 2004). On-site recycling of pavement materials has proven to be successful for pavement structure rehabilitation, but questions remain on whether or not on-site recycled pavement materials can increase pavement foundation quality.…”
Section: List Of Figuresmentioning
confidence: 99%
“…Recent experience with on-site recycling of pavement materials has been documented as a sustainable (Cross, Kearney, Justus, & Chesner, 2010;Lee, Mueller, & Singh, 2014) and cost effective (Bemanian, Polish, & Maurer, 2006;Diefenderfer, Apeagyei, Gallo, Dougald, & Weaver, 2012;Mallick, Bonner, Bradbury, Andrews, Kandhal, & Kearney, 2002;Miller, Kestler, Amatrudo, Eaton, & Hall, 2011;Stroup-Gardiner, 2012) solution for pavement rehabilitation. Several cases have demonstrated successful use of on-site pavement recycling rehabilitation techniques by transportation agencies (Bemanian et al, 2006;Diefenderfer et al, 2012;Lewis, Jared, Torres, & Mathews, 2006;Mallick et al, 2002;Maurer, Bemanian, & Polish, 2007;Miller et al, 2011;Romanoschi, Hossain, Gisi, & Heitzman, 2004;Wen, Tharaniyil, Ramme, & Krebs, 2004). On-site recycling of pavement materials has proven to be successful for pavement structure rehabilitation, but questions remain on whether or not on-site recycled pavement materials can increase pavement foundation performance.…”
Section: Introductionmentioning
confidence: 99%